Consolidation to the invariant kind of curves of low density polyethylene flow - Сівецький, Володимир Іванович; Рябінін, Дмитро Дмитрович; Сокольський, Олександр Леонідович; Кривко, Сергій Антонович; Табатабаі, Дарбагі Сайєд Мохамад Алі (Eastern-European Journal of Enterprise Technologies, 2012)
The objective of this article is estimation of acceptability of use of hydraulic radius for calculation of non-Newtonian liquids flow in nonround-form channels and determination of their rheological characteristics